PENTINGNYA MANAJEMEN DALAM PENGELOLAAN PENDIDIKAN - Mariah Mariah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2010)
Education have the vital role as individual impeller and society citizen to reach for the progresivitas at all of lini life. Despitefully, education can become the determinant of[is necessary for process of transformasi personal and also social. And in fact this is education idealism requiring the existence of enableness. But in ideal tataran, paradigm friction which is initially looking into education institute as social institute, is nowadays viewed as by an wet business farm is which indication of the importance of management change. the Management change of rhythm have to with the epoch demand